2017
DOI: 10.1177/1463949117719553
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of early childhood mathematics education: A systematic review of the literature focusing on practicing and prospective teachers

Abstract: This article presents the results of a literature review spanning 15 years (2000–2015), identifying empirical research relating to early childhood mathematics education. A total of 1141 articles were identified and examined in order to determine the current state of research in terms of location, participants, research questions, and the research methodology commonly used in this body of literature. Following a discussion of the overarching view of the literature, the authors present an analysis of a subsectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 135 publications
(160 reference statements)
0
17
0
Order By: Relevance
“…There is still no clear concept of how EC teacher education should be structured (Linder & Simpson, 2017). Our results provide at least initial indications from an emotional psychological perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is still no clear concept of how EC teacher education should be structured (Linder & Simpson, 2017). Our results provide at least initial indications from an emotional psychological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Research on early childhood (EC) teachers has increased enormously in recent years (Linder & Simpson, 2017). Studies have shown that EC teachers’ professional competence is important for the cognitive development of children in different domains such as mathematics (Duncan & National Institute of Child Health & Human Development Early Child Care Research Network, 2003; Krajewski & Schneider, 2009).…”
Section: Concept Of Achievement Emotions and Teacher Emotionsmentioning
confidence: 99%
“…The results show that the elements of the learning scenario related to the PST actions present a low frequency. This is considered to be influenced by two factors: these relate to teaching competencies that require time and practice to develop [50], and the context of the learning scenario refers to the systematization and remediation of learning.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of early education in mathematics for children's competence development cannot be neglected and is of growing interest in research (Linder and Simpson 2017). Developing children's mathematical competence requires structured and systematic learning environments (Benz et al 2016).…”
Section: Introductionmentioning
confidence: 99%